Levels of TNF-Î± in PBMC (Peripheral Blood Mononuclear Cells) Induced by Recombinant Non Structural 1 Protein of Dengue Virus Serotype-2 in vitro - FITHRIYAH SJATHA; OKTIVIA CHANDRA MUSTIKA; BETI ERNAWATI DEWI; TJAHJANI MIRAWATI SUDIRO (Indonesian Society for microbiology, 2019)
Dengue infection is a global health problem with an increasing incidence every year and now endemic in more than 100 WHO countries. Dengue infection is caused by dengue virus (DENV) which is an RNA virus with positive single strand, with Â±11kb genome size encoding 3 structural proteins, 7 non-structural proteins, and two Untranslated Region (UTR). NS1 protein is known to have a very important role in the development of severe DENV infection, by the direct effect causing host cells damage and indirect effect by activating immune response to induce the secretion of excess cytokines. This study aims to evaluate whether recombinant pcNS1 plasmids which have been proven expressing recombinant NS1 proteins in previous studies is able to induce cytokine secretion from Peripheral Blood Mononuclear Cells (PBMC). Transfected Chinese Hamster Ovary-K1 (CHO-K1) cells with recombinant pcNS1 plasmid was co-cultured with PBMC from healthy donor. After 48 h post co-cultured, cell supernatant was collected and TNF-Î± levels and NS1 recombinant were measured by ELISA. The results showed that recombinant NS1 protein was expressed in CHO-K1 mammalian cell line and able to induce TNF-Î± with higher levels compared to control.